The relationship between medical students' media use and learning progress. Issue 10 (3rd October 2021) - Nagel, Marie-Theres; Reichert-Schlax, Jasmin; Zlatkin-Troitschanskaia, Olga; Klose, Verena; Weber, Maruschka; Roeper, Jochen
ABSTRACT: The acquisition of warranted domain-specific knowledge is essential for practical work in medicine. The medical field, however, suffers from 'information overload', and students and physicians rely on access to verified, up-to-date information. Based on prior research, we investigated (1) which media medical students use for learning, (2) how their media use changes over the course of studies, and (3) how their media use and changes therein influence their acquisition of medical knowledge. Moreover, we examined (4) the influence of factors such as media overload. In a pre-post design, we assessed the development of students' medical knowledge before (T1) and after (T2) attending physiology seminars, and examined the relationship between their knowledge development and media use. Our analyses showed a significant increase in students' domain-specific knowledge after the seminars. In contrast, their media use behavior did not change substantially, with online sources being used more frequently than textbooks and course materials. An increased use of additional textbooks and online sources from T1 to T2 was linked to a stronger increase in knowledge. The results indicate that students' media use behavior influences their knowledge gain over their course of study, which has important implications for developing curricula in medical education.